2022
DOI: 10.1002/cbin.11912
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase gene mutations and bioinformatics of telocytes in hepatocellular carcinoma

Abstract: Telocytes (TCs) have crucial functions to promote the metastasis of hepatocellular carcinoma (HCC) by over-expressing matrix metalloproteinases (MMPs), but the mechanism by which TCs secrete MMPs in the genome is still unknown. We first cultured and isolated primary TCs from distinct liver cancer tissues and hepatic hemangioma surrounding tissues (Control group). Their whole exon genes were tested by Illumina HiSeq family of platforms and by high-throughput sequencing as well as variant mutations. Moreover, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Matrix metalloproteinase (MMP) is considered to be an important component of tumor invasion in gastric cancer and a useful marker used to determine the biological aggressiveness of gastric cancer, and inhibition of the expression of these genes has a tumor-suppressive effect. [ 68 , 69 ] On the other hand, MMPs were found to be highly correlated with the microenvironment of tumors and immune cells, and Youqiong Ye et al [ 70 ] found that MMP2 and MMP9 regulate tumor immune checkpoints by modulating PD - L1. Liu Bo et al [ 71 ] also found immunolocalization of MMP9 and MMP2 in osteolytic metastasis of human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase (MMP) is considered to be an important component of tumor invasion in gastric cancer and a useful marker used to determine the biological aggressiveness of gastric cancer, and inhibition of the expression of these genes has a tumor-suppressive effect. [ 68 , 69 ] On the other hand, MMPs were found to be highly correlated with the microenvironment of tumors and immune cells, and Youqiong Ye et al [ 70 ] found that MMP2 and MMP9 regulate tumor immune checkpoints by modulating PD - L1. Liu Bo et al [ 71 ] also found immunolocalization of MMP9 and MMP2 in osteolytic metastasis of human breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that genetic alterations have an important impact on the cancer prognosis ( 22 , 23 ). This research also showed that MMP1 had the highest mutation frequency in CESC, and the mutation frequency in HNSC was third in all tumor types, which was agreed with earlier studies reporting that genetic alterations in MMP1 were associated with HNSC ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] In cancer specimens, TCs exhibit gene heterogeneity on specific chromosomes, indicating their diverse effects on tumor cell behavior, such as cell signaling, expansion, movement, tumorigenesis, and inflammatory resistance. [ 10 , 11 ] TCs can be distinguished from other interstitial cell subtypes based on their unique microRNAs, immunohistochemical biomarkers, and immunofluorescent incorporation techniques. Immunohistochemical and immunofluorescent staining for biomarkers such as cluster of differentiation 34 (CD34) and platelet-derived growth factor receptor alpha (PDGFRA) can be used to identify TCs in cancer tissues, while negative expression for CD31 and vimentin helps differentiate TCs from other cell types.…”
mentioning
confidence: 99%